CENTRALITY OF FINANCING REFORM IN PERFORMANCE OF WORLD BANK FINANCED AGRICULTURAL PROJECTS IN TRANS-NZOIA COUNTY, KENYA - Wanyama, Makokha Peter; Wambugu, Dr. Lydia N.; Keiyoro, Prof. Peter (International Journal of Entrepreneurship and Project Management, 2020)
Purpose of the Study: The purpose of this study was to examine the centrality of financing reform in the performance of Agricultural projects funded by the World Bank in Trans-Nzoia County, Kenya. Methodology: This study adopted descriptive survey design with a focus on mixed-mode approach. The target population of the study was 800 farmers and 15 project officials. The study sample size was 268 respondents determined using simplified Yamane formula of proportions. Quantitative data was collected using a structured questionnaire with 12 Likert-type questions while the qualitative data was collected using standardized interview guide and focus group discussions. The study was grounded on pragmatism philosophy; paradigm that complements epistemological, methodological and axiological underpinnings desired by mixed methods research approach. The primary data collected was analyzed descriptively and inferentially using frequency distribution (mean, percentages and standard deviation) and multiple regression analysis with the aid of the Statistical Package for Social Sciences (SPSS), version 20.0. Findings: Financing reform had statistically significant influence on the performance of agricultural projects to an extent of r =0.244, (p-value< 0.01). The value of R2 was 0.244 indicating that financing reform explained 24.4% of the variation in the performance of agricultural projects. The Î² coefficient of 0.194 indicates a unit increase in financing reform led to 19.4% change in project performance. Unique Contribution to Theory, Practice and Policy: This study enriches the theory of project financing and provides documented analysis and answers the questions critical for credibility and utilization of the theory. In terms of policy, considering that the government of Kenya is working to develop systems and structures to ensure development projects are delivered within the confines of time, cost, resources and client satisfaction, this study therefore, has unique implications to government policy since it provides evidence to support policy formulation. The study contributes immensely to growth of project management discipline by providing empirical data critical in bridging the gap between the desired and actual project results.